Staphylococcus aureus in the community: colonization versus infection. - Maureen Miller; Heather A Cook; E Yoko Furuya; Meera Bhat; Mei-Ho Lee; Peter Vavagiakis; Paul Visintainer; Glenny Vasquez; Elaine Larson; Franklin D Lowy (PLoS ONE, 2009)
Antibiotic-resistant Staphylococcus aureus infections have increased dramatically in the community, yet S. aureus nasal colonization has remained stable. The objectives of this study were to determine if S. aureus colonization is a useful proxy measure to study disease transmission and infection in community settings, and to identify potential community reservoirs.Randomly selected households in Northern Manhattan, completed a structured social network questionnaire and provided nasal swabs that were typed by pulsed field gel electrophoresis to identify S. aureus colonizing strains. The main outcome measures were: 1) colonization with S. aureus; and 2) recent serious skin infection. Risk factor analyses were conducted at both the individual and the household levels; logistic regression models identified independent risks for household colonization and infection.321 surveyed households contained 914 members. The S. aureus prevalence was 25% and MRSA was 0.4%. More than 40% of households were colonized. Recent antibiotic use was the only significant correlate for household colonization (p = .002). Seventy-eight (24%) households reported serious skin infection. In contrast with colonization, five of the six risk factors that increased the risk of skin infection in the household at the univariate level remained independently significant in multivariable analysis: international travel, sports participation, surgery, antibiotic use and towel sharing. S. aureus colonization was not significantly associated with serious skin infection in any analysis. Among multiperson households with more than one person colonized, 50% carried the same strain.The lack of association between S. aureus nasal colonization and serious skin infection underscores the need to explore alternative venues or body sites that may be crucial to transmission. Moreover, the magnitude of colonization and infection within the household suggests that households are an underappreciated and substantial community reservoir.